The National Curriculum of Basic Education in debate: children’s rights and limits of parental responsibility - Ramírez Huaroto, Beatriz May Ling (2019)
In January of 2017, an acción popular lawsuit was admitted against the National Curriculum of Basic Education. The plaintiff, represented by six people, claimed that the Curriculum transgressed the “right of parents to choose the education of their children based on their own convictions”. Six months later, the court resolved to cancel some of the references to the gender equality approach in the Curriculum, noting that it was not the result of a deliberative process. This article argues that the debate ignores the fact that children’s rights are related but autonomous of their caregivers. Also, the scope of an education with a gender approach has not been determined yet, putting in danger the implementation of an education which allows to build a plural citizenship.